A comparison for donor-acceptor interactions between E(PH3)2 and NHEMe ligands (E = C to Pb) of W(CO)5 complexes using energy decomposition analysis method with natural orbitals for chemical valence theory - Phuong Loan, Huynh Thi; Hoa, Le Thi; Quang, Duong Tuan; Sy, Tran Duc; Hiep, Dang Tan; Tat, Pham Van; Ai Nhung, Nguyen Thi (Vietnam Journal of Chemistry, 2016)
Quantum chemical calculations at the BP86/TZ2P+ level of theory are performed for a comparison of density functional theory (DFT) between tetrylones [(CO)5W-E(PH3)2] (W5-EP2) and tetrylenes [(CO)5W-NHEMe] (W5-NHEMe) when E = C to Pb. The EDA-NOCV results suggest that the W-E bond dissociation energies (BDEs) in tetrylone complexes increase from the lighter to the heavier homologues. The W-E bond dissociation energies (BDEs) trend in W5-EP2 comes from the increase in (CO)5W←E(PH3)2 donation and strong electrostatic attraction, and that the ligands E(PH3)2 (EP2) are strong s-donors and very weak π-donors. The W-E BDEs trend in tetrylene complexes W5-NHEMe is opposite to that of the W5-EP2 complexes which decrease from the lighter to the heavier homologues. The NHEMe ligands are strong s-donors and weak π-acceptors. NOCV pairs were used in a description of the chemical bond between the W(CO)5 fragment and the ligands in the transition-metal complexes and the results indicated that the NOCV pairs lead to very valuable description of the bonding situation of the fragment-ligand bond in complexes. Keywords. Density functional theory; Bond dissociation energies (BDEs); Energy decomposition analysis (EDA); Natural Orbitals for Chemical Valence (NOCV)